Effects of Biogas Residues on Dissipation of Difenoconazole in Paddy Sediment System Under Field Conditions - Yu, Lina; Wen, Yong; Luo, Xuhui; Xiang, Yun; Yuan, Xufeng; Pang, Sen; Ma, Xiaodong; Li, Xuefeng (Frontiers in Environmental Science, 2022)
Little is known about whether the application of biogas residues in rice field will affect the degradation of pesticides. This study investigated the dissipation behavior of fungicide difenoconazole in paddy water and soil after application of chemical fertilizer or biogas residues. The results showed that the application of biogas residues changes the dissipation of difenoconazole in both paddy water and soil. The half-lives of difenoconazole in paddy water and soil with biogas residues were 0.50 d and 14.17 d respectively, while the half-lives of difenoconazole in paddy water and soil with chemical fertilizer were only 0.22d and 11.71d respectively. After biogas residues was applied in paddy field, no significant changes in pH value of paddy water and soil and soil microorganisms were observed, but soil organic matter decreased by 30%. The decrease of organic matter may be one of the reasons for the longer half-life of difenoconazole in paddy field. The above study provides a new focus on the scientific and rational use of biogas residues as organic fertilizer in rice field.